2018
DOI: 10.1002/2017jc013578
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Surface Thermal Forcing to Mixing in the Ocean

Abstract: A critical ingredient of the meridional overturning circulation (MOC) is vertical mixing, which causes dense waters in the deep sea to rise throughout the stratified interior to the upper ocean. Here, we report a laboratory study aimed at understanding the contributions from surface thermal forcing (STF) to this mixing process. Our study reveals that the ratio of the thermocline thickness to the fluid depth largely determines the mixing rate and the mixing efficiency in an overturning flow driven by STF. By ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…We stress that the definitions in (2.12) and (2.13) are also applicable in other thermal convection systems. For example, thermal convection with mixed boundary conditions (Wang, Huang & Xia 2017) (see figure 3b) and horizontal convection (Hughes & Griffiths 2008;Wang et al 2016;Wang, Huang & Xia 2018a) (figure 3c). For horizontal convection, since heating and cooling happen on the same height at the two ends of the cell, the vertical heat flux is always zero (see (2.12)), and only the horizontal component Nu H survives.…”
Section: Generalization Of the Nusselt Numbermentioning
confidence: 99%
“…We stress that the definitions in (2.12) and (2.13) are also applicable in other thermal convection systems. For example, thermal convection with mixed boundary conditions (Wang, Huang & Xia 2017) (see figure 3b) and horizontal convection (Hughes & Griffiths 2008;Wang et al 2016;Wang, Huang & Xia 2018a) (figure 3c). For horizontal convection, since heating and cooling happen on the same height at the two ends of the cell, the vertical heat flux is always zero (see (2.12)), and only the horizontal component Nu H survives.…”
Section: Generalization Of the Nusselt Numbermentioning
confidence: 99%
“…Moreover, as it was shown recently in Wang, Lohse & Shishkina (2021), HC is closely related to internally heated convection, where the thermal driving is not due to specific thermal boundary conditions but a bulk thermal source. A number of recent theoretical, experimental and numerical studies are dedicated to the transport properties and large-scale circulation in HC under various boundary conditions (Wang & Huang 2005;Sheard & King 2011;Griffiths, Hughes & Gayen 2013;Shishkina, Grossmann & Lohse 2016;Shishkina & Wagner 2016;Passaggia et al 2017a;Passaggia, Scotti & White 2017b;Shishkina 2017;Wang, Huang & Xia 2018;Ramme & Hansen 2019;Reiter & Shishkina 2020;Tsai et al 2020). However, current understanding of the thermal BL structure in HC remains rather limited.…”
Section: Introductionmentioning
confidence: 99%
“…2016; Passaggia et al. 2017 a ; Passaggia, Scotti & White 2017 b ; Shishkina 2017; Wang, Huang & Xia 2018; Ramme & Hansen 2019; Reiter & Shishkina 2020; Tsai et al. 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it was inferred that surface thermal forcing alone cannot sustain the turbulence level and the amount of viscous dissipation observed in the ocean (Paparella & Young 2002;Wang & Huang 2005). A recent experiment conducted by Wang, Huang & Xia (2018) supports this argument, and suggests that surface thermal forcing is less vital than the mechanical sources for the MOC. However, the study conducted by Hughes, Hogg & Griffiths (2009) indicated that the importance of surface thermal forcing is reflected in terms of its contribution in generating available potential energy and maintaining irreversible diapycnal mixing, rather than producing interior viscous dissipation and the oceanic kinetic energy.…”
Section: Introductionmentioning
confidence: 99%